2021
DOI: 10.1016/j.trsl.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Back and neck pain: in support of routine delivery of non-pharmacologic treatments as a way to improve individual and population health

Abstract: Back and neck pain: in support of routine delivery of nonpharmacologic treatments as a way to improve individual and population health,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 70 publications
5
16
0
9
Order By: Relevance
“…Initial contact with a DC has been shown to be associated with lower cost than most HCPs, while early access to physical therapy has had mixed total episode cost outcomes [25,27,46,47]. Our study also substantiated the findings of a recent narrative review that suggested that access to non-pharmacologic providers is associated with improved guideline concordance for treatment of spinal pain [48]. Reordering the sequencing of services in the early management of LBP has been proposed to systematically align clinical practice with the evidence-based CPGs [26,46,47,49].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Initial contact with a DC has been shown to be associated with lower cost than most HCPs, while early access to physical therapy has had mixed total episode cost outcomes [25,27,46,47]. Our study also substantiated the findings of a recent narrative review that suggested that access to non-pharmacologic providers is associated with improved guideline concordance for treatment of spinal pain [48]. Reordering the sequencing of services in the early management of LBP has been proposed to systematically align clinical practice with the evidence-based CPGs [26,46,47,49].…”
Section: Discussionsupporting
confidence: 78%
“…CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) is associated with improved guideline concordance for treatment of spinal pain [48]. Reordering the sequencing of services in the early management of LBP has been proposed to systematically align clinical practice with the evidence-based CPGs [26,46,47,49].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“… 51 , 52 For non-pharmacologic approaches like PIPT, part of the contextual considerations that have impacted its uptake include provider beliefs. 1 On the positive side, physical therapists are known for their patient-centered approaches to care through the use of tools like shared-decision making and patient-centered communication. 53 , 54 However, physical therapy training is still heavily focused on biomedical approaches for treating musculoskeletal pain which could make adoption of PIPT more difficult.…”
Section: Moving Towards Wide-scale Implementationmentioning
confidence: 99%
“…There has been substantial growth in interest in biopsychosocial treatments for patients with musculoskeletal pain. 1 One reason for this increased interest is the American College of Physicians Clinical Practice Guidelines and the Centers for Disease Control and Prevention Guidelines for treatment of chronic pain. 2 , 3 Additionally, the revised International Association for the Study of Pain (IASP) definition for pain focuses on the influence of biological, psychological, and social factors on a person’s pain experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation